2018
DOI: 10.1016/j.ctro.2018.01.005
|View full text |Cite|
|
Sign up to set email alerts
|

Anti PD-L1 DUrvalumab combined with Cetuximab and RadiOtherapy in locally advanced squamous cell carcinoma of the head and neck: A phase I/II study (DUCRO)

Abstract: HighlightsHead and neck squamous cell carcinoma is an immune suppressive malignancy.Conventional intensification strategies didn’t provide any incremental benefit.Inhibiting the PD-1/PD-L1 checkpoint may synergize with cetuximab and radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…PD‐L1 immunoexpression in TCs and/or ICs is a useful clinical biomarker to select patients who may benefit the most from immune check‐point inhibitors. Evaluation of PD‐L1 IHC has been included as either companion or supplementary tests in multiple anti‐PD1/anti‐PD‐L1 clinical trials of various cancers . Therefore, it becomes increasingly important for practising pathologists to provide reliable and consistent interpretation of PD‐L1 IHC across different tumour types, as it is of paramount importance in determining the eligibility for anti‐PD‐L1/anti‐PD1 therapy and to predict treatment benefits.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PD‐L1 immunoexpression in TCs and/or ICs is a useful clinical biomarker to select patients who may benefit the most from immune check‐point inhibitors. Evaluation of PD‐L1 IHC has been included as either companion or supplementary tests in multiple anti‐PD1/anti‐PD‐L1 clinical trials of various cancers . Therefore, it becomes increasingly important for practising pathologists to provide reliable and consistent interpretation of PD‐L1 IHC across different tumour types, as it is of paramount importance in determining the eligibility for anti‐PD‐L1/anti‐PD1 therapy and to predict treatment benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, PD‐L1 and PD‐1 have emerged as a key check‐point that can be manipulated with inhibitory monoclonal antibodies in various cancer types. Multiple prospective randomised clinical trials have shown promising results of PD‐1/PD‐L1 immune check‐point inhibitors in a variety of cancer types, including a subset of patients with urothelial carcinoma (UC), breast carcinoma (BC) and head and neck squamous cell carcinoma (HSCC), leading to the Food and Drug Administration (FDA) approval of several anti‐PD‐1/PD‐L1 agents …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations